Authentic interpretation - Endicott, T (Wiley, 2020)
I approach the identification of the principles of legal interpretation through a discussion of an important but largely forgotten strand in our legal heritage: the idea (and at some points in English law, the rule) that the interpretation of legislation is to be done by the lawmaker. The idea that authentic interpretation is interpretation by the lawmaker united the Roman emperors Constantine and Justinian with Bracton, Aquinas, King James I of England, Hobbes, and Bentham. Already in the early 17th century, a new modern approach was emerging in England. The modern approach separates the interpretive power from the legislative power, and allocates the interpretive power to an independent court. I argue that there are some cogent, general considerations in favour of the modern approach. But it is worth identifying the elements of good sense that made it seem that the interpretive power ought to be reserved for the lawmaker. And it is worth identifying the drawbacks in the modern approach; I argue that they are highly relevant to the complex question of how judges ought to interpret legislation.